Two 3.9 ppm/°C curvature-corrected band gap voltage references with fast and low-power start ups. Issue 1 (2nd January 2017) - Mollasalmani, J.; Ghaznavi-Ghoushchi, M. B.
ABSTRACT: High-precision devices are among the important applications as well as demands on ultra-low temperature coefficient (TC) band gap voltage references (BGRs). This paper presents two ultra-low TC BGRs with fast and low-power start up. The proposed circuits used temperature from a compensation block, which consisted of one resistor and one PMOS transistor. The voltage references utilised the peak current source to prepare a temperature-independent reference output voltage. They produced an output voltage of 1.135 V, which exhibited a temperature coefficient of only 3.9 ppm/°C when temperature varied from −40°C to 50°C at a supply voltage of 1.8 V. The start-up current was limited to 51.91 nA for the proposed BGR2 and gained a low power feature. In addition, the start-up circuit had a total power consumption of only 0.0004% in the proposed BGR 2. The simulations were fully done with 0.18 µm CMOS technology.